Subcritical CO2 adsorption on geomaterials of coal-bearing strata in the context of geological carbon sequestration - Maram Almolliyeh; Snehasis Tripathy; Sivachidambaram Sadasivam; Shakil Masum; Sara Edwards Rassner; Andy Mitchell; Hywel Rhys Thomas (International Journal of Coal Geology, 2023)

“We’re always an afterthought”- Designing tobacco control campaigns for dissemination with and to LGBTQ +—serving community organizations: a thematic analysis - Shoba Ramanadhan; Meg Salvia; Elaine Hanby; Anna C. Revette; Madison K. Rivard; N. F. N. Scout; Julia Applegate; Bob Gordon; Ana Machado; Mitchell R. Lunn; Juno Obedin-Maliver; Jennifer Potter; et al. (Cancer Causes & Control, 2023)
Purpose Evidence-based health communication campaigns can support tobacco control and address tobacco-related inequities among lesbian, gay, bisexual, transgender, and queer (LGBTQ +) populations. Community organizations focused on LGBTQ + health (e.g., nonprofits, community centers, and community health centers) can be prime channels for delivering evidence-based health communication campaigns. However, it is unclear how to balance the goals of a) designing campaigns to support broad adoption/uptake and b) adaptation addressing the needs of diverse communities and contexts. As part of an effort to support “designing for dissemination,” we explored the key challenges and opportunities staff and leaders of LGBTQ + -serving community organizations encounter when adopting or adapting evidence-based health communication campaigns. Methods A team of researchers and advisory committee members conducted this study, many of whom have lived, research, and/or practice experience with LGBTQ + health. We interviewed 22 staff members and leaders of community organizations serving LGBTQ + populations in the US in early 2021. We used a team-based, reflexive thematic analysis approach. Results The findings highlight the challenges of attempting to use health communication campaigns misaligned with the assets and needs of organizations and community members. The three major themes identified were as follows: (1) available evidence-based health communication campaigns typically do not sufficiently center LGBTQ + communities, (2) negotiation regarding campaign utilization places additional burden on practitioners who have to act as “gatekeepers,” and (3) processes of using health communication campaigns often conflict with organizational efforts to engage community members in adoption and adaptation activities. Conclusions We offer a set of considerations to support collaborative design and dissemination of health communication campaigns to organizations serving LGBTQ + communities: (1) develop campaigns with and for LGBTQ + populations, (2) attend to the broader structural forces impacting campaign recipients, (3) support in-house testing and adaptations, and (4) increase access to granular data for community organizations.

Regional variability in peatland burning at mid-to high-latitudes during the Holocene - Thomas G. Sim; Graeme T. Swindles; Paul J. Morris; Andy J. Baird; Angela V. Gallego-Sala; Yuwan Wang; Maarten Blaauw; Philip Camill; Michelle Garneau; Mark Hardiman; Julie Loisel; Minna Vӓliranta; et al. (Quaternary Science Reviews, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

Demonstration of the Feasibility of Predicting the Flow of Pharmaceutically Relevant Powders from Particle and Bulk Physical Properties - Hervé Barjat; Stephen Checkley; Toma Chitu; Neil Dawson; Amin Farshchi; Ana Ferreira; John Gamble; Michael Leane; Andy Mitchell; Chris Morris; Kendal Pitt; Richard Storey; et al. (Journal of Pharmaceutical Innovation, 2021)

Temperature-related mortality impacts under and beyond Paris Agreement climate change scenarios - Ana Maria Vicedo-Cabrera; Yuming Guo; Francesco Sera; Veronika Huber; Carl-Friedrich Schleussner; Dann Mitchell; Shilu Tong; Micheline de Sousa Zanotti Staglior Coelho; Paulo Hilario Nascimento Saldiva; Eric Lavigne; Patricia Matus Correa; Nicolas Valdes Ortega; et al. (Climatic Change, 2018)

How to Replicate the Functions and Biodiversity of a Threatened Tree Species? The Case of Fraxinus excelsior in Britain - Ruth J. Mitchell; Robin J. Pakeman; Alice Broome; Joan K. Beaton; Paul E. Bellamy; Rob W. Brooker; Chris J. Ellis; Alison J. Hester; Nick G. Hodgetts; Glenn R. Iason; Nick A. Littlewood; Gabor Pozsgai; et al. (Ecosystems, 2016)

Factors modulating cottongrass seedling growth stimulation to enhanced nitrogen and carbon dioxide: compensatory tradeoffs in leaf dynamics and allocation to meet potassium-limited growth - Andy Siegenthaler; Alexandre Buttler; Philippe Grosvernier; Jean-Michel Gobat; Mats B. Nilsson; Edward A. D. Mitchell (Oecologia, 2013)